The effect of prior long-term recellularization with keratocytes of decellularized porcine corneas implanted in a rabbit anterior lamellar keratoplasty model. - Ahearne, Mark (My University, 2021)
Decellularized porcine corneal scaffolds are a potential alternative to human cornea for keratoplasty. Although clinical trials have reported promising results, there can be corneal haze or scar tissue. Here, we examined if recellularizing the scaffolds with human keratocytes would result in a better outcome. Scaffolds were prepared that retained little DNA (14.89 ± 5.56 ng/mg) and demonstrated a lack of cytotoxicity by in vitro. The scaffolds were recellularized using human corneal stromal cells and cultured for between 14 in serum-supplemented media followed by a further 14 days in either serum free or serum-supplemented media. All groups showed full-depth cell penetration after 14 days. When serum was present, staining for ALDH3A1 remained weak but after serum-free culture, staining was brighter and the keratocytes adopted a native dendritic morphology with an increase (p < 0.05) of keratocan, decorin, lumican and CD34 gene expression. A rabbit anterior lamellar keratoplasty model was used to compare implanting a 250 μm thick decellularized lenticule against one that had been recellularized with human stromal cells after serum-free culture. In both groups, host rabbit epithelium covered the implants, but transparency was not restored after 3 months. Post-mortem histology showed under the epithelium, a less-compact collagen layer, which appeared to be a regenerating zone with some α-SMA staining, indicating fibrotic cells. In the posterior scaffold, ALDH1A1 staining was present in all the acellular scaffold, but in only one of the recellularized lenticules. Since there was little difference between acellular and cell-seeded scaffolds in our in vivo study, future scaffold development should use acellular controls to determine if cells are necessary.
PUBLISHED
Keywords: Keratocytes; Scaffolds; Cornea; Transplantation